Anemia Management Among Pregnant and Postpartum Women in Thailand’s Southern Border Provinces: An Ethnographic Study - Chemama, Nisreen; Hayee, Fusiyah; Siriphan, Siriphan; Yodkaew, Urai; Maropi, Anuchit; Walohtae, Warakorn Fa-is; Jarintanan, Punyisa; Doloh, Surawut (Princess of Naradhiwas University Journal, 2025)
Background and Objective This ethnographic qualitative research aimed to explore the sociocultural phenomena influencing the management of anemia among pregnant and postpartum women in Thailand’s southern border provinces. Methods Data were collected through in-depth interviews, focus group discussions, and continuous field observations with 20 key informants, including pregnant women, postpartum mothers, and family members were purposively selected from in Khok Khian and Bukit subdistricts in Narathiwat province and Yaring subdistrict in Pattani province, data were analyzed using thematic analysis. Results The findings revealed three major themes regarding how anemia is managed among pregnant and postpartum women in the southern border area: 1) pregnant women’s physical and lifestyle experiences, 2) beliefs and attitudes of pregnant women and their families, including perceptions of prenatal supplements, iron-rich foods, and misunderstandings influenced by religious and cultural beliefs, and 3) social factors involving pregnant women’s mothers, husbands, husband’s mother, and community leaders, all of whom play roles in anemia management. Conclusion and Recommendation The findings underscore the need for culturally responsive and family-centered health interventions to improve maternal nutrition and anemia prevention within Muslim communities in southern Thailand.